Integrating carbonyl iron with sponge to enable lightweight and dual-frequency absorption. (25th February 2019) - Quan, Bin; Gu, Weihua; Chen, Jiabin; Xu, Guoyue; Ji, Guangbin
Abstract: In this work, sponge impregnated with iron pentacarbonyl was utilized to obtain a novel composite in which the carbonyl iron (CI) was embedded in a graphitized carbon matrix (CI-C). The CI that results from the thermal pyrolysis of iron pentacarbonyl can homogeneously disperse into the pore structures of the sponge skeleton, which not only improves the stability of the CI, but also modifies the impedance matching character. Moreover, the sponge bulk turns into graphitized carbon during the heat treatment (graphitized catalysis of magnetic metal on carbon at high temperature). Due to the respective strong dissipation ability of CI and the graphitized carbon matrix, the as-prepared CI-C sample exhibits a good microwave absorption performance, including expanding the effective absorption bandwidth and reduced weight, compared to pure CI. Moreover, the sample with 30 wt% paraffin loading not only shows strong reflection loss absorbing ability, but also possesses continuous dual-absorption peaks (9.96 GHz, −38.7 dB, and 13.8 GHz is −37.6 dB). This work not only extends the application of carbonyl iron as a lightweight microwave absorber with dual-absorption peaks but also initiates a new approach for artificially designed carbon-based composites via a simple sponge-impregnation method.